Competenze comunicative e relazioni interpersonali - Paola Della Valle (RiCognizioni, 2023)
The Communicative Approach or CLT was a revolution in applied linguistics in the 1990s and is still the last theoretical framework in TEFL. It aroused great enthusiasm at the time but was also subject to some criticism. In Italian Secondary Schools it was never fully applied and did not leave a relevant mark on the didactics of the English language. At present, most Italian university students in foreign languages and literatures, and future teachers of English, still show the imprint of a traditional language learning experience that owes much to deductive reasoning, a structural syllabus, and even the influence of the Grammar-Translation Method. This essay investigates the reasons why CLT was not so successful in the Italian context, considers its future prospects in the current “post-method” period, and envisages possible solutions for an effective approach in language teaching that combines tradition and innovation, the achievement of institutional requirements and of students’ interaction, and the development of communicative competence and accuracy.